The use of sentinel skin islands for monitoring buried and semi-buried micro-vascular flaps. Part II: Clinical application - Molitor, Martin; Mestak, Ondrej; Pink, Richard; Foltan, Rene; Sukop, Andrej; Lucchina, Stefano (Biomedical papers, 2021)
Despite the high success rate of micro-vascular flaps, anastomosis compromise occurs in 5-10% and that can lead to flap failure. Reliable monitoring of the flap is therefore of similar importance to that of the precise surgical procedure itself. Multiple methods have been reported for monitoring of the flap vitality, the first one being direct visual monitoring. In buried flaps direct visualisation is not feasible or is unreliable. In these cases we can extend the buried flap to expose a segment of it to act as a monitoring sentinel. For the purpose of this review we used our clinical experience as a starting point, and for the extended information and expertise we conducted a search of the PubMed database. Over 40 monitoring techniques have been reported to-date. Direct visual monitoring is still generally used method with a reliability of up to 100% and an overall success rate of up to 99%. Direct visualisation remains as the simplest, cheapest and yet a very reliable method of flap monitoring. In this review we provide a description of various possible techniques for externalising part of a buried flap, define the tissues that can be used for this purpose and we summarise the procedures that should be followed to achieve the best reliability and validity of monitoring the skin island.
Keywords: free flap; sentinel skin paddle; monitoring skin paddle; sentinel skin island; monitoring skin island; buried flap